2012
DOI: 10.3748/wjg.v18.i47.7079
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharides can regulate cytokine and P-glycoprotein expression in H22 tumor-bearing mice

Abstract: APS exerts a synergistic anti-tumor effect with ADM in H22 tumor-bearing mice. This may be related to its ability to enhance the expression of IL-1α, IL-2, IL-6, and TNF-α, decrease IL-10, and down-regulate MDR1 mRNA and P-GP expression levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 28 publications
0
49
0
Order By: Relevance
“…In addition, it was reported that long-term treatment of genistein could induce the related protein expression of first-pass metabolism in mice [14,15] and the activities of phase II metabolic enzymes in mice could be mediated by oligosaccharides [13,16,17]. Moreover, some non-digestible carbohydrates, such as hyaluronan oligosaccharides and astragalus polysaccharides, were shown to inhibit P-gp, MRP1, and MRP2 expression, thereby contributing to an increase in intracellular concentration of food ingredients or drugs [18,19]. Accordingly, we suppose that stachyose promoting absorption of genistein may be closely related to inhibition of first-pass metabolism of genistein in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that long-term treatment of genistein could induce the related protein expression of first-pass metabolism in mice [14,15] and the activities of phase II metabolic enzymes in mice could be mediated by oligosaccharides [13,16,17]. Moreover, some non-digestible carbohydrates, such as hyaluronan oligosaccharides and astragalus polysaccharides, were shown to inhibit P-gp, MRP1, and MRP2 expression, thereby contributing to an increase in intracellular concentration of food ingredients or drugs [18,19]. Accordingly, we suppose that stachyose promoting absorption of genistein may be closely related to inhibition of first-pass metabolism of genistein in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…To seek effective herbs or herbal components to reverse drug resistance has become one of research focuses in liver cancer study. Astragalus polysaccharides have been reported to be potent to enhance antitumor effects of adriamycin in H22 hepatocarcinoma by upregulating IL1α, IL2, IL6, and TNFα, downregulating IL10 and multidrug resistance protein 1 (MDR1) [199] . Astragaloside Ⅱ, another component from HuangQi (Astragalus membranaceus), is effective to increase 5Fu cytotoxicity toward 5Fu resistant Bel7402/Fu cells accompanied by down regulation of Pgp (Pglycoprotein), phosphorylation of ERK1/2, p38 and JNK [200] .…”
Section: Reversal Of Drug Resistancementioning
confidence: 99%
“…Among these, Astragalus polysaccharides (APS) has been most extensively studied, which is demonstrated to have substantial pharmacological applications, including anti-cancer, anti-inflammatory, immunomodulatory and antioxidant effects. APS plays its affiliated anticancer role by strengthening immune function (Liu et al, 2010;Zhao et al, 2011), counteracting the negative effects of chemotherapeutic drugs and enhancing the sensitivity of chemotherapeutics (Tian et al, 2012).…”
Section: Protective Effect Of Astragalus Polysaccharides On Liver Injmentioning
confidence: 99%